Fractures in sub-Saharan Africa: epidemiology, economic impact and ethnography (Fractures-E3): study protocol [version 1; peer review: 2 approved] - Christopher Grundy; Simon Matthew Graham; Hannah Wilson; Samuel Hawley; Kebba Marenah; Tadios Manyanga; James Masters; Bintou Trawally; Munyardardzi Ndekwere; Prudance Mushayavanhu; Mkhululi Lukhele; Rachael Gooberman-Hill; et al. (Wellcome Open Research)
Background: The population of older adults is growing in sub-Saharan Africa. Ageing exponentially increases fragility fracture risk. Of all global regions, Africa is projected to observe the greatest increase in fragility fractures. Fractures cause pain, disability and sometimes death, and management is expensive, often requiring complex healthcare delivery. For countries to plan future healthcare services, understanding is needed of fracture epidemiology, associated health service costs and the currently available healthcare resources. Methods: The Fractures-E3 5-year mixed-methods research programme will investigate the epidemiology, economic impact, and treatment provision for fracture and wider musculoskeletal health in The Gambia, South Africa and Zimbabwe. These three countries are diverse in their geography, degree of urbanisation, maturity of health service infrastructure, and health profiles. The programme comprises five study types: (i) population-based cross-sectional studies to determine vertebral fracture prevalence. Secondary outcomes will include osteoarthritis and sarcopenia. Age- and sex-stratified household sampling will recruit 5030 adults aged 40 years and older; (ii) prospective cohort studies in adults aged 40 years and older will determine hip fracture incidence, associated risk factors, and outcomes over one year (e.g. mortality, disability, health-related quality of life); (iii) economic studies of direct health costs of hip fracture with projection modelling of future national health costs and cost-effectiveness analyses of different hip fracture care pathways; (iv) national surveys of hip fracture services (including traditional bonesetters in The Gambia); and (v) ethnographic studies of hip fracture care provision and experiences will understand fracture service pathways. Conclusions: Greater understanding of current and expected fracture burdens, fracture risk factors, and existing fracture care provision, is intended to inform national clinical guidelines, health service policy and planning and future health service development in sub-Saharan Africa.